Postponing the decay of entanglement and quantum coherence for maximally entangled mixed states under the action of correlated noise channels - Awasthi, Natasha; Singh, Ashutosh; Kumar Joshi, Dheeraj (Frontiers in Quantum Science and Technology, 2023)
We investigate the dynamics of a maximally entangled mixed state (MEMS) under the action of correlated noise channels. The channel acts in a way that its successive uses are correlated. We have studied the properties such as quantum coherence and entanglement of the MEMS. For partially correlated channels, both the entanglement and coherence of MEMS are found to decay much slower than that for the memoryless channels. Moreover, we observe a freezing effect of coherence for phase-damping as well as depolarizing channels and freezing of entanglement for phase-damping channels with perfect memory. For amplitude-damping and depolarizing channels, memory helps in either delaying the sudden death of entanglement or slowing down the decay rate of coherence. These observations suggest that memory channels perform better than memoryless channels in maintaining the integrity of quantum states and their utility in quantum information processing protocols.